Factors affecting the medication taking behaviour of psychiatric patients: a preliminary study from central Nepal - Poudel, Ramesh Sharma; Shrestha, Shakti; Prajapati, Aastha; Piryani, Rano Mal (Journal of Chitwan Medical College, 2017)
Abstract on the PDF.